Cold mix asphalt- an alternative method to pavement rehabilitation - Mohamad Taher, Mohammad Nasir; Bujang, Hazirah (Penerbit UTHM, 2021)
Failure or distress on pavement surface such as pothole, alligator cracking and shear cracking that commonly occurred and required pavement rehabilitation for maintenance proposes. Regarding the cost of reconstruction and the cost of transport and storing removed pavement materials, paying attention to recycling strategies for asphalt pavements has been considered extremely by transportation agencies [1] Pavement rehabilitation is considered as cost efficient instead of reconstruction for new pavement. Pavement rehabilitation is a structural or functional enhancement of a pavement which produces a substantial extension in service life, by substantially improving pavement condition and ride quality. The characteristic of existing pavement conditions is an important component of any rehabilitation design methodology.